Ethanol in aqueous hydrogen peroxide solution: Hydrothermal synthesis of highly photoluminescent carbon dots as multifunctional nanosensors. (November 2015) - Hu, Yaoping; Yang, Jing; Jia, Li; Yu, Jun-Sheng
Abstract: A novel synthetic strategy has been developed for facile, green and low-cost fabrication of highly photoluminescent carbon dots (C-dots) by hydrothermal treatment of ethanol in aqueous hydrogen peroxide (H2 O2 ) solution. Noticeably, the synthesized C-dots present an unexpectedly large quantum yield of 38.7% without any post-treatments. In contrast to the most amorphous C-dots, the ethanol-derived C-dots possess an essentially crystalline nature as evidenced by the high-resolution transmission electron microscopy and selected-area electron diffraction. It is found that the C-dots can serve as multifunctional fluorescence nanosensors to detect pH, temperature, and the concentration of hypochlorite ion (ClO − ). The PL intensity of C-dots decreases dramatically as pH increases from 3 to 11. Based on this feature, a C-dots coated fluorescent paper for visual detection of pH by naked eyes has been successfully prepared. The C-dots reveals a linear and reversible PL response toward the temperature in the range of 10–80 °C, suggesting the great potential for design of temperature-sensitive devices. The selective quantification of ClO − concentration from 0.1 to 10 μM with a detection limit as low as 0.08 μM is achieved by ClO − -induced PL quenching of C-dots. Moreover, the C-dots applied for ClO − assay in real water samples with satisfactory recovery is demonstrated.